2018
DOI: 10.1038/s41598-018-24378-z
|View full text |Cite
|
Sign up to set email alerts
|

Intact interleukin-10 receptor signaling protects from hippocampal damage elicited by experimental neurotropic virus infection of SJL mice

Abstract: Theiler’s murine encephalomyelitis virus (TMEV) infection represents an experimental mouse model to study hippocampal damage induced by neurotropic viruses. IL-10 is a pleiotropic cytokine with profound anti-inflammatory properties, which critically controls immune homeostasis. In order to analyze IL-10R signaling following virus-induced polioencephalitis, SJL mice were intracerebrally infected with TMEV. RNA-based next generation sequencing revealed an up-regulation of Il10, Il10rα and further genes involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 95 publications
1
17
0
1
Order By: Relevance
“…A recent study demonstrated that the severity of hippocampal neurodegeneration, the number of activated microglia/macrophages, and the ISG15 expression almost perfectly discriminate seizing from non-seizing C57BL/6 mice after a TMEV-DA infection despite the fact that strong microglia/macrophage activation and some hippocampal damage are also present in SJL mice [23]. Limited hippocampal damage in TMEV-BeAn-infected SJL mice might be caused by the induction of IL10 receptor signaling, which exhibits anti-inflammatory and neuroprotective properties [162,163,164]. No difference between SJL and C57BL/6 mice can be found in the TGFβ1 gene expression during acute polioencephalomyelitis, but seized C57BL/6 mice show a strong TGFβ expression in hippocampal neurons, which is not present in unseized C57BL/6 mice or mock- and TMEV-DA-infected SJL mice [2,164].…”
Section: Innate Immunity In Theiler’s Murine Encephalomyelitis Virmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that the severity of hippocampal neurodegeneration, the number of activated microglia/macrophages, and the ISG15 expression almost perfectly discriminate seizing from non-seizing C57BL/6 mice after a TMEV-DA infection despite the fact that strong microglia/macrophage activation and some hippocampal damage are also present in SJL mice [23]. Limited hippocampal damage in TMEV-BeAn-infected SJL mice might be caused by the induction of IL10 receptor signaling, which exhibits anti-inflammatory and neuroprotective properties [162,163,164]. No difference between SJL and C57BL/6 mice can be found in the TGFβ1 gene expression during acute polioencephalomyelitis, but seized C57BL/6 mice show a strong TGFβ expression in hippocampal neurons, which is not present in unseized C57BL/6 mice or mock- and TMEV-DA-infected SJL mice [2,164].…”
Section: Innate Immunity In Theiler’s Murine Encephalomyelitis Virmentioning
confidence: 99%
“…In TMEV-DA-infected mice, IL1β does not seem to play a major role in seizures because IL1 receptor I- and MyD88-deficient C57BL/6 mice have a seizure frequency similar to wild type mice. In contrast, only 10% of TNF receptor I- and 15% of IL6-deficient C57BL/6 mice showed signs of seizure activity, and fewer seizures are seen in TNFα −/− mice bred on a C57BL/6 background [98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152,153,154,155,156,157,158,159,160,161,162,163,…”
Section: Innate Immunity In Theiler’s Murine Encephalomyelitis Virmentioning
confidence: 99%
“…In the TMEV-mediated transient polioencephalitis model using SJL mice, peak virus load in the hippocampus coincides with peak expression of IL-10, IL-10ra , and relates genes. IL-10R neutralization resulted in increased loss of mature neurons and axonal damage, which correlated with enhanced inflammation, although virus load was not altered (65). Further, increased accumulation of Foxp3 Tregs and arginase-1 expressing microglia/macrophages suggested unsuccessful efforts of the host to compensate for the abrogated IL-10 signaling.…”
Section: Il-10: the Gamekeeper Of Tissue Damage During Chronic Jhmv Imentioning
confidence: 99%
“…IL-10 is mostly regarded as an anti-inflammatory cytokine that plays a central role in a variety of human diseases through the maintenance of immune homeostasis [72]. Previous studies have revealed that Il-10 can prevent hepatic steatosis and other metabolic abnormalities with anti-inflammatory, immunosuppressive, tolerogenic, and neuroprotective properties [73,74,75]. The mechanism employed by the attenuated strain of DHAV-3 to stimulate anti-inflammatory cytokines remains unclear.…”
Section: Discussionmentioning
confidence: 99%